A Proposed Educational Vision For Activating The Role of The Jordanian Universities Students Families In Enhancing Students Intellectual Security From The Students Perspectives - Ahmad Rahamneh, Khloud Falah; Hamed Al- Qudah, Mohammed Amin (European Scientific Journal, ESJ, 2016)
This study aimed to find out the role of the Jordanian families in establishing intellectual security in their children from the perspective of the Jordanian students enrolled in Jordanian universities. For this purpose, a questionnaire of 36 paragraphs was created. The questionnaire was divided into three domains: the social, the cultural and the religious domains. The study was conducted on a random sample of (2700) students from three public universities (the University of Jordan, Yarmouk University, Moa'ta University and Al-Balqa' Applied University) and three private universities (Amman Al-Ahliah, Azzaytouna al-Ordiniah and Jerash). The study was conducted during the second university term of 2015/2016 CE. The descriptive analytical approach was used. The study showed that the three domains (social, cultural and religious) were of high degree. The highest of them was the cultural domain. The two paragraphs which state (the family's quest to build a cultural system emerging from our religion, values, traditions and customs, consolidating the values of the theoretical and practical dimensions of moderation among children) occupied the first rank, followed by the social domain. The paragraph which states that (The family's doing its basic function of education and socialization) occupied the first rank, whereas the religious domain occupied the last one. The paragraph which states (The family's seeking to form the right belief at an early age) occupied the first rank.